Improving Writing Skill of Non-English Department Students Using AI (A Case Study on The Effectiveness of ChatGPT) - Tri Wahyuni; Nurlailatul Aqromi (Universitas Pendidikan Ganesha, 2026)
The integration of Artificial Intelligence (AI) into education has gained increasing attention, particularly in enhancing writing skills for non-English department through English for Specific Purposes (ESP). This study examines the effectiveness of ChatGPT in improving writing quality, with a specific focus on clarity, coherence, and accuracy. Employing a quasi-experimental design, the research compares an experimental group using ChatGPT with a control group following traditional writing instruction. Data were collected through writing assessments, surveys, and interviews. The findings indicate a significant improvement in the experimental group’s writing performance, especially in clarity and coherence, alongside greater confidence and autonomy fostered by personalized feedback from ChatGPT. The study contributes to the growing body of literature on AI-assisted language learning by highlighting ChatGPT’s potential as a supportive tool for writing instruction, while emphasizing the continued importance of lecturer’s guidance to complement automated suggestions. Further research is needed to explore AI applications in more specialized disciplines and to assess their long-term impact on writing development